2020
DOI: 10.1111/ppe.12662
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric acute lymphoblastic leukaemia and caesarean section: A report from the United Kingdom Childhood Cancer Study (UKCCS)

Abstract: Background:Reports have suggested that children born by caesarean initiated before labour onset may be at increased risk of developing acute lymphoblastic leukaemia (ALL). However, with most data being derived from case-control study interviews, information on the underpinning reasons for caesarean section is sparse, and evidence is conflicting. Objectives:Use clinical records compiled at the time of delivery to investigate the association between childhood ALL and caesarean delivery; examining timing in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Thirty studies were excluded due to the following reasons: a lack of relevant data ( n = 16); a non‐original article ( n = 8); basic science ( n = 3); data source duplication ( n = 2); and data unavailability ( n = 1). Finally, 16 relevant articles 1,6,9–22 included ten case‐control studies, five cohort studies, and one pooled analysis. The data from the original study were excluded in this pooled analysis to avoid double counting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty studies were excluded due to the following reasons: a lack of relevant data ( n = 16); a non‐original article ( n = 8); basic science ( n = 3); data source duplication ( n = 2); and data unavailability ( n = 1). Finally, 16 relevant articles 1,6,9–22 included ten case‐control studies, five cohort studies, and one pooled analysis. The data from the original study were excluded in this pooled analysis to avoid double counting.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have found a link between CS and leukemia, with contradictory results. Several studies 6,9–15 established a relationship between CS and leukemia, particularly for elective CS 1,12,16–19 . In contrast, some studies found no overall link between CS and leukemia 1,17,19–21 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, over 90 peer-reviewed articles containing UKCCS data have been published, and a full list is available on the study website (www.UKCCS.org). Assembling data from multiple sources, key reports include ALL genome-wide association studies (GWAS),14 20 and those examining the potential aetiological roles of a wide range of biological (eg, infections/markers of infectious exposure),21–23 physical (eg, ionising/non-ionising radiation)12 13 24 25 and chemical (eg, prescription drugs/smoking) agents acting on parents before the child’s conception and the child during pregnancy/early life,10 26 27 as well as relationships with other illnesses (eg, allergy) and birth characteristics (eg, birth weight) 21 28 29. Importantly, the UKCCS accessed medical records to help answer key questions relating to prescription drugs, illness histories and comorbidities; such contemporaneously recorded information, which by its nature is free from differential recall bias, often producing very different results from that obtained by self-report 11 22 30 31…”
Section: Findings To Datementioning
confidence: 99%